FYN regulates aqueous humor outflow and IOP through the phosphorylation of VE-CADHERIN - Krishnakumar Kizhatil; Graham M. Clark; Daniel K. Sunderland; Aakriti Bhandari; Logan J. Horbal; Revathi Balasubramanian; Simon W. M. John (Nature Communications)
Abstract Schlemm’s canal endothelial cells (SECs) serve as the final barrier to aqueous humor (AQH) drainage from the eye. SECs adjust permeability to AQH outflow to modulate intraocular pressure (IOP). The broad identification of IOP-related genes implicates SECs in glaucoma. However, the molecular mechanisms by which SECs sense and respond to pressure changes to regulate fluid permeability and IOP remain largely undefined. We hypothesize that mechano-responsive phosphorylation of the cell adhesion molecule VE-CADHERIN (CDH5) in SECs, by FYN and possibly other SRC family kinases, regulates adherens junction (AJ) permeability to AQH in response to IOP. On experimentally raising IOP in mouse eyes, AJ permeability, CDH5 phosphorylation, and FYN activation at the AJ all increase. FYN null mutant mice display disrupted IOP regulation and reduced AQH outflow. These findings demonstrate an important role of mechanotransducive signaling within SECs in maintaining IOP homeostasis and implicate FYN as a potential target for developing IOP-lowering treatments.